Hitting the sweet spot -workbook - Fortini - Campbell, Lisa (Chicago: Copy Workshop, 1992)
Sus temas principales son: Sec .The sweet sport. Why hitting the sweet spot works. you already know more than you think. Sec 2- How to find the sweet spot, learn to read yourself. Laying the foundation. Sec 3- Form insight to inspiration Mapping out perceptions. Segmenting people. Sec 4- Consumer insight at work, The account planning revolution. The role of the account planner.
Incluye bibliografía
Keywords: Publicidad